The New Globalisation: From Too Big to Fail to Too Intertwined to Decouple - Simone Urbani Grecchi (Intereconomics, 2022)
Going forward, international elites should instead strive for the application of one of the most liberal-minded principles of this current world order: self-determination.
Keywords: F23; F52; F53; H77; 330